The w' balance model: mathematical and methodological considerations - Skiba, P. F.; Clarke, D. C. (International Journal of Sports Physiology and Performance, 2021)
The power-duration relationship is of interest to athletes, coaches, and sport scientists because it provides insights into the athlete`s physiology and performance capabilities. Traditionally, this relationship is measured using laboratory-based time-to-exhaustion trials of differing durations. In cycling, the availability of bike-mounted power meters enables the power-duration relationship to be computed as best-power-for-duration efforts, which may also be extracted from the maximal mean power profile.1 Various mathematical models have been proposed to express the power-duration relationship in terms of physiologically interpretable parameters.2 One such construct is the 2-parameter CP (critical power) model, which describes the capacity of an individual to sustain particular work rates as a function of time. In this way, the model summarizes the relationship between exercise intensity and duration for an individual. The model can be expressed in several algebraically equivalent ways,3 but is perhaps most easily visualized in the following formulation (Figure 1):